Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/10428190802270886
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial pneumonitis during rituximab-containing chemotherapy for non-Hodgkin lymphoma

Abstract: Rituximab is widely used for CD20+ non-Hodgkin lymphoma (NHL). The use of rituximab has been uncommonly associated with pulmonary toxicity. We report here a single institution experience on the clinical characteristics, diagnosis, treatment and outcome of rituximab-induced interstitial lung disease. From May 2007 to February 2008, 107 patients with NHL received rituximab-containing chemotherapy. Among them, nine patients were identified who developed interstitial pneumonitis during rituximab-containing chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
10

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 19 publications
0
51
0
10
Order By: Relevance
“…Of the 45 patients, 17 (38%) were in Asia, 12 were in the Americas (and their ethnic origin was not reported) and 16 were in Europe. The rate of occurrence was 8.4% (nine out of 107) in the Korean case series [39] and 11% (four out of 36) in the Dutch case series [38]. The reason for rituximab therapy was diffuse large B-cell lymphoma in 30 patients, indolent lymphoma in 10 (mantle cell lymphoma (n52) [20,21,39], marginal zone lymphoma or mucosaassociated lymphoid tissue (MALT) (n53) [22,32,33], follicular lymphoma (n54) [24,32,39] and Waldenströ m's macroglobulinaemia (n51) [38]), chronic lymphocytic leukaemia in two [3,37], ITP in two [18,26] and RA in one [16].…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 45 patients, 17 (38%) were in Asia, 12 were in the Americas (and their ethnic origin was not reported) and 16 were in Europe. The rate of occurrence was 8.4% (nine out of 107) in the Korean case series [39] and 11% (four out of 36) in the Dutch case series [38]. The reason for rituximab therapy was diffuse large B-cell lymphoma in 30 patients, indolent lymphoma in 10 (mantle cell lymphoma (n52) [20,21,39], marginal zone lymphoma or mucosaassociated lymphoid tissue (MALT) (n53) [22,32,33], follicular lymphoma (n54) [24,32,39] and Waldenströ m's macroglobulinaemia (n51) [38]), chronic lymphocytic leukaemia in two [3,37], ITP in two [18,26] and RA in one [16].…”
Section: Characteristics Of the Patientsmentioning
confidence: 99%
“…1) [3,, described in anecdotal case reports and in nine case series reporting two cases [16,21,29,34,35], three cases [19,33], four cases [38] or nine cases [39]. A few adequately documented cases occurred during clinical trials.…”
Section: Number Of Articles Retrieved and Numbers Of Included And Excmentioning
confidence: 99%
“…According to Wagner's review, hypoxemia and saturation of blood oxygen decreasing is uniformly abnormal in RTX-ILD [14]. There's also research signify fever was the most common presenting symptom [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore mainly used to treat non-Hodgkin lymphoma and chronic lymphocytic leukemia without compromising humeral immunity. Although the incidence of rituximab-induced interstitial lung disease was estimated to be very rare by the manufacturer (<0.03 %), more recent studies reported an incidence of 3.5-11 % Iu et al 2008 ;Nieuwenhuizen et al 2008 ). The CT pattern most often described is (sub)acute OP followed by NSIP (Lioté et al 2010 ).…”
Section: Rituximabmentioning
confidence: 99%